“The Authors” Make Me Think Equally of Women and Men: Exploring Mixed-Gender Representations in a Visual Categorisation Task - Kim Jonathan D.; Öttl Anton; Gygax Pascal; Behne Dawn M.; Hyönä Jukka; Gabriel Ute (De Gruyter, 2025)
Abstract: A common goal for gender-fair language policies is to promote terms that elicit balanced activation of gender categories. Expanding previous research on the activation of feminine versus masculine categories through person nouns, we used a word-picture response priming design with gendered human faces as target stimuli, to explore whether a simultaneous activation of more than one gender category can be captured empirically. Focusing on Norwegian (Bokmål), we tested whether reading stereotypical (i.e. role nouns, e.g. “care givers”) and categorical gendered person nouns (i.e. name pairs, e.g. “Elin and Sandra”) facilitates the categorisation of face pairs that match the gender of the designated people. In Experiment 1 (N = 32), gender-specific (feminine or masculine) word primes were tested, before gender-balanced word primes (non-stereotyped role nouns; pairs of a female and a male name) were added in Experiment 2 (N = 39). In both experiments, the visual targets were pairs of faces (two female faces, two male faces, or one male and one female face). Consistent with previous results for English, we found gender-specific priming effects, supporting the notion that gender categories activated by linguistic stimuli may also exert influence outside of language processing. Most importantly, mixed-gender faces were successfully primed by non-stereotypical role nouns providing initial support for the idea of a balanced activation of gender categories.